Discoid lupus and human immunodeficiency virus: A retrospective chart review to determine the prevalence and progression of co-occurrence of these conditions at a single Academic Center - Aimee Two; Jessica Kim So; Taraneh Paravar (Wolters Kluwer Medknow Publications, 2017)
Context: Discoid lupus erythematosus (DLE) and human immunodeficiency virus (HIV) are both disorders of the immune system. The pathophysiology of these diseases varies greatly as DLE is characterized by an overactive immune system that attacks normal host cells, whereas HIV is characterized by an exogenous attack on the immune system that depletes it of key cell types. Although the reason is unknown, co-occurrence of DLE and HIV is rare. Aims: The goal of this study is to determine the prevalence of co-occurrence of DLE and HIV and to determine whether patients with both DLE and HIV share any clinical feature. Subjects and Methods: The medical records of all patients seen within a single academic health center over a 20-year period were reviewed to determine the prevalence of cutaneous lupus, HIV, and co-occurrence of these conditions. The charts of patients diagnosed with both conditions were further reviewed to determine similarities between them. Results: Of the 10,719 patients diagnosed with HIV and 182 patients diagnosed with cutaneous lupus, only 2 patients were diagnosed with both conditions. Both of these patients were diagnosed with DLE several years after being diagnosed with HIV. They had an undetectable HIV viral load, normal CD4 T-cell counts, and were on antiretroviral therapy when diagnosed with DLE. Conclusion: These results confirm that co-occurrence of DLE and HIV is rare. Although our study population was small, findings from these patients suggest that in HIV-positive patients, DLE manifestations occur when their HIV disease activity is minimal.